Copper and lead ions removal by electrocoagulation: process performance and implications for energy consumption - prasetyaningrum, aji prasetyaningrum (International Journal of Renewable Energy Development)
Electroplating wastewater contained a high amount of heavy metals that can cause serious problems to humans and the environment. The aim of this research to examine the electrocoagulation (EC) effect of removing copper and lead ions from wastewater using aluminum electrodes. It also analyzes the removal efficiency and energy consumption rate of the effects in heavy metals removal from wastewaters, via electrocoagulation method. The operational parameters were the electrocoagulation time (20â€“40) min, current density (40â€“80) A/m2, pH (3-11), and initial concentration of heavy metals. The concentration of metals ions and sludges morphology was analyzed using AAS and SEM, respectively. The percentage of lead and cooper ions decrease with increasing EC time. The current density was an important parameter. The use of high current density has an effect on increasing energy consumption. Furthermore, the performance of the electrocoagulation process was decreased at low pH. The higher initial concentration of heavy metals results in higher removal efficiency than lower concentration. The removal percentage of copper and lead ions was 89.88% and 98.76%, respectively at 40 minutes with electrocoagulation treatment of 80 A/m2 current density and pH 9. For this condition, the speciï¬c amount of dissolved electrodes was 0.2201 kg/m3 with energy consumption of 21.6 kWh/m3. The kinetic study showed ion removal following the pseudo-first-order model. The sludges produced by the electrocoagulation process contain economic compounds and have potential as new material.